Peranan Bahasa Inggris Dalam Era Masyarakat Ekonomi Asean (MEA): Bagaimana Sistem Pembelajaran Bahasa Inggris Yang Islami Di Indonesia? - Sri Supiah Cahyati (STAI Siliwangi Bandung, 2015)
In early 2016 the Indonesian enters the ASEAN Economic Community (AEC). It has become the demands of the changing times as part of a global community. Interaction between these nations require global communications. Everything and all levels of society will take part in the international market, so it will be left behind and unable to compete if we do not master the English language. It was a common knowledge, to improve competitiveness is the ability to speak English. In the era of AEC Indonesia will compete with foreign workers and the rise of economic competition will be more stringent. This inevitably raises the need for the Indonesian to English language skills in order to master communication. Methods of teaching English until now do not reflect the preparation of human resources to take part in the global community. Learning and understanding the English language becomes a necessity that cannot be avoided. Can our English teaching methods answer the demands of the Islamic global community? This is what needs to be formulated in the content of curriculum materials in English lessons at formal schools, especially Islamic schools, such as: MI, MTs, MA, and Islamic University.